Kontribusi Sikap dan Motivasi Belajar Siswa terhadap Hasil Belajar Bahasa Indonesia - Zulhafizh .; Atmazaki .; Syahrul R (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: This study background the problem low average yield learning Indonesian annually on national exams. In addition, many students who didn’t pass this final exam each year and didn’t want to follow the remedial activities for students who are not yet complete, so it will affect the learning outcomes achieved. Therefore, the need to do an analysis of students’ attitudes and motivation toward learning outcomes. Sample of the research were 78 students. Subject of this study were obtained by using proportional sample. Data on attitudes and motivation to learn is by using a questionnaire valid as level and reliability, while Indonesian learning outcomes is rapor. Analysis of data using simple correlation technique, partial correlation, and regression with correlation Product Moment. The results showed that (1) there is a positive and significant relationship between the attitude of learning with Indonesian learning outcomes, (2) there is a positive and significant relationship between learning motivation outcomes Indonesian language, and (3) there is a positive and significant relationship together attitude and motivation to learn with Indonesian learning outcomes. Kata kunci: sikap, motivasi belajar, hasil belajar bahasa Indonesia